Ectodermal Wnt Controls Nasal Pit Morphogenesis Through Modulation of the BMP/FGF/JNK Signaling Axis - Zhu, Xiao-Jing (Dev Dyn, 2016)
BACKGROUND: Mutations of WNT3, WNT5A, WNT9B, and WNT11 genes are associated with orofacial birth defects, including non-syndromic cleft lip with cleft palate in humans. However, the source of Wnt ligands and their signaling effects on the orofacial morphogenetic process remain elusive. RESULTS: Using Foxg1-Cre to impair Wnt secretion through the inactivation of Gpr177/mWls, we investigate the relevant regulation of Wnt production and signaling in nasal–facial development. Ectodermal ablation of Gpr177 leads to severe facial deformities resulting from dramatically reduced cell proliferation and increased cell death due to a combined loss of WNT, FGF and BMP signaling in the developing facial prominence. In the invaginating nasal pit, the Gpr177 disruption also causes a detrimental effect on migration of the olfactory epithelial cells into the mesenchymal region. The blockage of Wnt secretion apparently impairs the olfactory epithelial cells through modulation of JNK signaling. CONCLUSIONS: Our study thus suggests the head ectoderm, including the facial ectoderm and the neuroectoderm, as the source of canonical as well as noncanonical Wnt ligands during early development of the nasal–facial prominence. Both β-catenin–dependent and –independent signaling pathways are required for proper development of these morphogenetic processes.